Evaluation of Indian durum wheat germplasm for the presence of Sr36 gene for resistance to pathotypes of stem rust race 117-group - and A.N. MISHRA, SUSHIL K. SINGH, T.L. PRAKASHA, A. DIVYA, S.L. KANTWA, S.V. SAI PRASAD* (Indian Phytopathology, 2013)
India is one of the major durum wheat (Triticum turgidum var. durum) producers with around 2.5 million tonnes production per year and has the potential to export this wheat to the world market. In India, durum wheat is grown mostly in the states of Madhya Pradesh, Maharashtra, Rajasthan, Gujarat, Uttar Pradesh and Karnataka. Durum wheat cultivation offers many advantages like saving irrigation water due to its high water-use efficiency, field tolerance to loose smut and Karnal bunt diseases, employment generation through durum based fast food industry and provide better nutrition as it is rich in protein, Î²-carotene and essential micronutrients like iron and zinc. Among the rust diseases of wheat, stem rust caused by Puccinia graminis f. sp. tritici has been particularly severe on durum wheat.